2023
DOI: 10.1186/s40479-023-00217-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative experiences of adolescents with borderline personality disorder: description and prediction

Abstract: Aims The first purpose of this study was to assess the severity of dissociative experiences reported by adolescent inpatients with borderline personality disorder (BPD). The second purpose was to compare the severity of their dissociative symptoms to those reported by a sample of adult inpatients with BPD. The third purpose of this study was to assess a range of clinically meaningful predictors of the severity of dissociation in adolescents and adults with BPD. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…BPD negatively impacts adolescents' physical and psychological well-being, which influences their lifespan; therefore, it is necessary to make a plan of treatment to intervene in the conditions to prevent the deterioration of BPD. The current study suggested that the treatment of adolescent BPD should be based on psychotherapy rather than medicine; nevertheless, medication, such as secondgeneration antipsychotics, was still a potent and useful adjunct for adolescent BPD [12]. Nonpharmacological, which focuses on psychotherapy, is preferable because of fewer physical adverse side effects [12].…”
Section: Predictors and Intervention In Bpd For Adolescentsmentioning
confidence: 89%
See 4 more Smart Citations
“…BPD negatively impacts adolescents' physical and psychological well-being, which influences their lifespan; therefore, it is necessary to make a plan of treatment to intervene in the conditions to prevent the deterioration of BPD. The current study suggested that the treatment of adolescent BPD should be based on psychotherapy rather than medicine; nevertheless, medication, such as secondgeneration antipsychotics, was still a potent and useful adjunct for adolescent BPD [12]. Nonpharmacological, which focuses on psychotherapy, is preferable because of fewer physical adverse side effects [12].…”
Section: Predictors and Intervention In Bpd For Adolescentsmentioning
confidence: 89%
“…Therefore, clinicians, psychotherapists, and staff in the community and schools should pay attention to the adolescents who experienced maltreatment, poverty, bullying, and sexual abuse in the past to intervene in borderline personality traits before it turns to become BPD. BPD is highly likely to appear as a complication with other mental disorders during adolescence; therefore, the mental disorders that the adolescent is diagnosed with can also be a predictor of BPD [12]. Previous research emphasized that eating disorders, the reason is binge eating, could be a symptom of BPD's risk behaviours among adolescents [12].…”
Section: Predictors and Intervention In Bpd For Adolescentsmentioning
confidence: 99%
See 3 more Smart Citations